Āyurvedīya khanija-vijñāna : rasa-gandhātmaka - Pratāpasiṃha, Kavirāja (Prakāśa Āyurvedīya Aushadhālaya aura Pustakālaya, 1931)
Study of mineralogy, materia medica, and therapeutics of the minerals and their compounds in Ayurvedic system in Indian medicine.